Pemberian Fraksi Daun Kemangi (Ocimum americanum L.) terhadap Spermatozoa Tikus Putih Jantan (Rattus norvegicus) - Vinnata, Nora Novia; Salni, Salni; Nita, Sri (Politeknik Kesehatan Tanjungkarang, 2018)
The major cause of a spermatogenetic process disorder in testis is free radical. One of the traditional medicines commonly used as an aphrodisiac is Kemangi plant. Rosary Basil leaf (Ocimum americanum L.), Indonesian name is Kemangi, contains active substances, such as flavonoid, saponin, tannin, and triterpenoid/steroid which is antioxidant and fertility. The purpose of the present research was to analyze the effect of testis weight, diameter, epithelium thickness, morphology, and spermatozoa amount of male white mouse (Rattus norvegicus) after feeding fractions of Kemangi leaf (Ocimum americanum L.) This study was experimental with a posttest-only control group design. The research sample size was 24 furrow male white mice Sprague Dawley, 60-74 days old. They were divided into 4 treatment groups, each being fed the fractions of n-hexane, ethyl acetate, and water-ethanol of Kemangi leaf at a dosage of 100 mg/mouse/day, compared to CMC 1% for the control group for 36 days, and then a dissection was done to take out secreted substances and to examine the histology of testis. The result showed that there were increases of testis weight in the treatment group as compared to that of the control (p=0.018). In addition, there were increases in diameter and thickness of seminiferous tubule epithelium of testis, in the morphology of abnormal sperm (p=0.000), and in spermatozoa amount (p=0.020). Fractions of Kemangi leaf can increase testis weight, diameter, and epithelium thickness, morphology, and spermatozoa amount of furrow male white mice Sprague Dawley, particularly the fraction of ethyl acetate.